Two centuries of arts and science in Nice and Villefranche sur Mer: 1) Pioneers: 1800 to 1900 - Christian Sardet (Arts et Sciences)
We tell the story of exploration of the flora and fauna in the Nice region, and especially pelagic organisms, the work of some twenty biologists associated with painters. In 1800, Antoine Risso, Jean Gabriel Prêtre, François Péron and Alexandre Lesueur described and painted flowers, fish and some marine invertebrates. In the middle of the century, Jean Baptiste Vérany, a naturalist from Nice, welcomed prestigious German and Swiss biologists - Johannes Müller, Rudolf Leuckart, Ernst Haeckel and Carl Vogt - who described andstudied little known organisms such as siphonophores and radiolarians. And in the 1880s, Hermann Fol, Jules Barrois and Alexis Korotneff set up a marine station in Villefranche sur Mer, recognized as an exceptional site for the study of plankton. During this period, the Natural History Museum of Nice was enriched by exceptional collections of flowers, fish and funghi assembled by Risso, Vérany and Jean Baptiste Barla, who employed Vincent Fossat for his talent as painter / illustrator. By the end of the century, the Nice region attracted foreign royalty and aristocrats, visiting biologists and impressionists painters. In a companion article (Sardet 2025 / 2 Modern era: 1970 to 2024) we show that organisms studied in the 19th century are still the subject of research at the Institut de la Mer de Villefranche (IMEV).